Exploring occupational standing activities using accelerometer-based activity monitoring. Issue 8 (3rd August 2019) - Anderson, Jennifer; Granat, Malcolm H.; Williams, Anita E.; Nester, Christopher
Abstract: Prolonged standing at work is required by an estimated 60% of the employed population and is associated with a high prevalence of musculoskeletal disorders. 'Standing' is expected to encompass a range of activities of varying intensity. This study aimed to define a range of 'standing' work-based activities; and objectively explore differences between 'standing' occupations. The following movements were defined using a triaxial accelerometer (ActivPAL) through recordings of known movements ( n = 11): static standing, weight-shifting, shuffling, walking and sitting. Movements over a working day were defined for chefs ( n = 10), veterinary surgeons ( n = 7) and office workers ( n = 9). Despite veterinary surgeons and chefs spending a similar time in an upright posture, veterinary surgeons spent 62% of this time standing statically whereas chefs split their time between all the movements. Overall, this study provides the first attempt to define 'standing' activities, allowing the differentiation of activities between occupations spending similar periods of time upright. Practitioner Summary: This study identified a range of work-based 'standing' activities of varying intensity. Differences in activity were recorded between two occupations spending a similar time in an upright posture (veterinary surgeons and chefs). A broader definition of standing activities could be important when considering factors related to musculoskeletal disorders at work.